Individualized approach to palliative care integration for patients with metastatic non-small cell lung cancer - Carley Mitchell; Roshni S. Kailar; Melinda L. Hsu (Frontiers in Medicine, 2026)
Early integration of palliative care is recommended for all patients with advanced solid tumor malignancies. However, this practice has not been widely adopted for various reasons. Recent therapeutic advancements along with improved understanding of tumor biology have contributed to greater prognostic uncertainty and changes in symptom burden, highlighted nicely within the metastatic non-small cell lung cancer population. These changes call for a more nuanced approach to palliative care referral which could be facilitated through patient reported outcome monitoring and disease related triggers.